2018
DOI: 10.3390/rs10030476
|View full text |Cite
|
Sign up to set email alerts
|

IMF-Slices for GPR Data Processing Using Variational Mode Decomposition Method

Abstract: Using traditional time-frequency analysis methods, it is possible to delineate the time-frequency structures of ground-penetrating radar (GPR) data. A series of applications based on time-frequency analysis were proposed for the GPR data processing and imaging. With respect to signal processing, GPR data are typically non-stationary, which limits the applications of these methods moving forward. Empirical mode decomposition (EMD) provides alternative solutions with a fresh perspective. With EMD, GPR data are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This study uses the VMD method [22][23][24][25]. It is a signal decomposition estimation method based on classical Wiener filtering [26,27], Hilbert transform [28] and mixing variational problem.…”
Section: Variational Mode Decomposition Methods Principlementioning
confidence: 99%
“…This study uses the VMD method [22][23][24][25]. It is a signal decomposition estimation method based on classical Wiener filtering [26,27], Hilbert transform [28] and mixing variational problem.…”
Section: Variational Mode Decomposition Methods Principlementioning
confidence: 99%
“…; Zhang et al . ). This paper highlights the seismic decomposition based on a new type of wavelet basis and the extended applications.…”
Section: Introductionmentioning
confidence: 97%
“…As the first issue discussed above, inspired by the nonstationary convolution in time-frequency domain (Margrave et al 2002), we propose a new type of wavelet basis in this paper based on the classic Ricker wavelet, where the seismic attenuation is considered and referred to as the quality factor Q. For the second issue, we have combined the multi-channel decomposition technique and the idea of OMP to form an improved algorithm, which we referred to as the multi-channel OMP in our recent research work, and the examples demonstrated sparser decomposition results Zhang et al 2018). This paper highlights the seismic decomposition based on a new type of wavelet basis and the extended applications.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the long-term program focused on the algorithms and applications of the GPR data time-frequency decomposition, this paper can be seen as a follow-up study of our previous work [18]. The research targets of this paper are to: (1) review the method of the f -x EMD and test its effectiveness on GPR data; (2) extend the original f -x EMD to the dip filter in f -x domain by reconstructing the frequency slices from the linear combination of different IMFs; (3) form the hybrid scheme by combining noise suppression based on SSA with sliding windows with the dip filter in f -x domain.…”
Section: Introductionmentioning
confidence: 99%